The Subtitling of Sexual Discourse in The Magdalene Sisters - de Morais Gehin, Antônia Elizângela; Fernandes, Alinne Balduino Pires (Revista Estudos Feministas, 2021)
This article sets out to analyse the translation of the discourse on sexuality within the scope of subtitling, more specifically, the transcodification of cultural references from a cultural translation point of view. This study adopts as corpus the subtitles of the film The Magdalene Sisters (2002), written and directed by Peter Mullan. In Brazil, the film was released in 2004, under the title Em Nome de Deus. Based on true facts, the plot tells the story of four women imprisoned for religious and moral reasons in institutions called Magdalen Asylums in the nineteen-sixties, in Ireland. The ultimate goal of this study is to unveil how women are represented through the subtitling of the discourse on sexuality. Furthermore, to investigate how the translation procedures - applied in the process of subtitling from English into Portuguese - reflects gender inequality and theologically-based misogyny, as well as the religious and moral ideologies that permeate the discourse on sexuality in the narrative. The corpus’s qualitative analysis of the corpus showed that the grammatical variations and the subtitler's interventions have promoted an approximation of the source and target contexts.